Investigating the Effectiveness and Implementation Challenges of Project-Based Learning: A Case Study of Public School Teachers in Chitwan, Nepal - Ananta Dhungana (Journal of Balkumari College, 2025)
The paper explores the effectiveness of Project-Based Learning (PBL) as an active learning strategy in Nepal, examining its impact on student engagement, skill development, and long-term learning outcomes within the country’s diverse educational contexts. Employing a qualitative approach, the study engaged 20 teachers from urban and rural public schools, covering disciplines such as English as a Foreign Language, Information and Communication Technology, and science. Qualitative data from teacher interviews and document review revealed challenges, including lack of teacher training, resource shortages, sociocultural barriers like gender and caste discrimination, and high costs, alongside facilitators such as teacher motivation, curriculum flexibility, and community involvement. Proposed solutions include professional development workshops, cost-effective project models, parental engagement, and curriculum reforms. The study concludes that PBL holds transformative potential for Nepal, fostering 21st-century skills and aligning with global standards, with recommendations for systemic support to ensure sustainable, inclusive implementation.